Poverty Dynamics : Measurement and Understanding from an Interdisciplinary Perspective /: Measurement and Understanding from an Interdisciplinary Perspective. (January 2008) - Addison, Tony; Hulme, David; Kanbur, S. M. Ravi, 1954-
No abstract available